2012
DOI: 10.1158/1078-0432.ccr-11-2757
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant L1 Cell Adhesion Molecule Affects Tumor Behavior and Chemosensitivity in Anaplastic Thyroid Carcinoma

Abstract: Purpose: Anaplastic thyroid carcinoma (ATC) is one of the most invasive human cancers and has a poor prognosis. Molecular targets of ATC that determine its highly aggressive nature remain unidentified. This study investigated L1 cell adhesion molecule (L1CAM) expression and its role in tumorigenesis of ATCs.Experimental Design: Expression of L1CAM in thyroid cancer was evaluated by immunohistochemical analyses of tumor samples from patients with thyroid cancer. We investigated the role of L1CAM in proliferatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Interestingly, there was a definite inverse relationship between these 2 features, indicating that L1 might be related with loss of differentiation in retinoblastoma. This finding was in line with previous reports on the expression of L1 in poorly differentiated cancers in other organs [13, 17]. Furthermore, in 4 human retinoblastoma tumor samples from patients who underwent enucleation despite multiple cycles of intravenous chemotherapy, diffuse L1 expression was observed, supporting the role of L1 in the chemoresistance of retinoblastoma.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, there was a definite inverse relationship between these 2 features, indicating that L1 might be related with loss of differentiation in retinoblastoma. This finding was in line with previous reports on the expression of L1 in poorly differentiated cancers in other organs [13, 17]. Furthermore, in 4 human retinoblastoma tumor samples from patients who underwent enucleation despite multiple cycles of intravenous chemotherapy, diffuse L1 expression was observed, supporting the role of L1 in the chemoresistance of retinoblastoma.…”
Section: Discussionsupporting
confidence: 91%
“…These observations suggested that overexpression of L1cam might be a common incidence in gastric cancer and could serve as an independent prognostic indicator to identify patients with different outcomes. In line with our study, up-regulation of L1cam was also found in other tumors, such as ovarian cancer, colorectal cancer, anaplastic thyroid carcinoma and intrahepatic cholangiocarcinoma [14,16,17,25]. However, further study is needed to confirm if L1cam could be used as a universal biomarker of prognosis for neoplasm.…”
Section: Discussionsupporting
confidence: 87%
“…37, 38 Furthermore, our group has recently reported that L1CAM has an important role in determining tumor behavior and chemosensitivity in anaplastic thyroid cancers. 39 On the basis of these findings, we postulated that L1CAM and YAP1 might have synergistic effects on epithelial to mesenchymal changes, resulting in the invasion of adjacent normal tissues. Compatible with our idea, IHC staining demonstrated membrane localization of L1CAM in shCOM tumor cells.…”
Section: Resultsmentioning
confidence: 97%